Synergistic effects of surfactant blends on lignite dust wettability - Xinhui Luo; Xueming Fang; Jie Liu; Henglin Liu; Jiajia Zou; Yuanxi Xu; Xingxing Liang; Wei Sun (PLoS ONE, 2025)
In this study, we employed a combination of theoretical and experimental analyses to explore the effects of the physico-chemical properties of lignite samples and surfactants on lignite dust’s wettability, thereby improving dust control in coal mines. First, we measured and analysed the coal samples’ industrial composition, elemental composition and chemical structure. It was found that the selected lignite dust has high ash and low moisture content and contains many hydrophobic functional groups, resulting in poor wettability by water. Next, we conducted surface tension tests, contact angle tests and lignite dust settling experiments to screen 12 monomer surfactants, exploring the impact of these solutions on lignite dust wettability. Finally, considering all monomer surfactants’ abilities to reduce surface tension, decrease contact angles and promote dust settling in solutions, we selected five surfactants (AES, MES-30, AEO-9, CDEA and CHSB) for blending based on their excellent performance in tests. We prepared the blends of these five surfactants, each with a mass fraction of 0.5 wt%, in a 1:1 ratio, resulting in 10 blended solutions. We measured the performance of these solutions and revealed that the AES + AEO-9 blend demonstrated a significant synergistic effect, markedly enhancing the capture efficiency of water for lignite dust.